Recent study on biodegradable hydrogels for agriculture application: A review - Wan Amirah Najwa, Wan Anuar; Ros Azlinawati, Ramli; El-Sayed, Marwa M.; Warkar, Sudhir G. (Elsevier Ltd, 2025)
Biodegradability and eco-friendliness are the most importance topic to consider in the development of new products. Commercial hydrogels for agriculture applications are made from fully synthetic polymers, which is non-biodegradable and harmful to environment. The utilization of polysaccharide in hydrogels production has sparked the rise of biodegradable hydrogels (BHs). However, using it alone results in poor mechanical properties and very fast degradation. Therefore, combining it with other materials as a composite is necessary. This article reviewed the development of BHs in the last 5 years. Classifications, materials resources, preparation methods, biodegradability of BHs, seeds germination and plant growth performance are critically investigated. Fundamental concepts such as definitions and application methods of BHs are described. Finally, important conclusions and outlook have been mentioned at the end of this article.